2016
DOI: 10.4321/s1889-836x2016000100005
|View full text |Cite
|
Sign up to set email alerts
|

Cambios inducidos en DKK1 en pacientes con artritis reumatoide que inician tratamiento con terapia biológica

Abstract: Introduction: The aim of this study is to assess the relationship among inflammatory charge, cardiovascular risk and bone metabolism in patients with rheumatoid arthritis initiating biological therapy treatment. Patients and methods: This is a prospective cohort study conducted in patients diagnosed with active rheumatoid arthritis (RA) assessed in the Rheumatology Unit and initiating biological therapy. Patients will be selected consecutively, with preliminary data on 14 patients. We present preliminary data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Our preliminary study showed a decrease in DKK1 levels after 6 months of treatment 26 , which was in agreement with that published by Briot et al 13 . In this article, patients with active RA treated with tocilizumab experienced a decrease in DKK1 concentrations, as well as a decrease in markers of bone formation at 3 and 12 months of treatment, not finding changes in the levels of sclerostin.…”
Section: Discussionsupporting
confidence: 94%
“…Our preliminary study showed a decrease in DKK1 levels after 6 months of treatment 26 , which was in agreement with that published by Briot et al 13 . In this article, patients with active RA treated with tocilizumab experienced a decrease in DKK1 concentrations, as well as a decrease in markers of bone formation at 3 and 12 months of treatment, not finding changes in the levels of sclerostin.…”
Section: Discussionsupporting
confidence: 94%